Mellan behov och självbestämmande - Biståndshandläggares upplevelser av etiska dilemman i arbetet med demenssjuka brukare utan sjukdomsinsikt - Appelberg,Ellen; Papamoshos,Andreas (2024)
This study aims to investigate how six social workers in elderly care in southern Sweden experience working with dementia patients without insight into their disease. The study focuses on the right to self-determination for dementia patients and how social workers handle the ethical dilemma regarding the user’s resistance to support despite the need for care interventions. The study is based on the qualitative method and the data was collected through semi-structured interviews. Further, the material was processed based on the thematic analysis, which led to three main themes that are presented in the results and analysis of the study. The results of the study showed that the social workers experienced both internal and external factors that gave rise to ethical dilemmas. The internal factors included the difficulty in reaching the client, providing the client with necessary information, and the uncertainty about whether the client could explain its needs. The uncertainty meant that the social worker often had to balance between the individual's self-determination and the risk of the client being harmed. Furthermore, the external factors consisted of constraints imposed by the organization's framework, such as lack of time, competence, and limited guidelines. To manage the internal and external factors, the case managers used different strategies such as adapted communication, motivational and relationship-building work, collaboration with relatives and other professionals, and different approaches to consent. The data material was analyzed from different ethical perspectives and allowed us to discern that the assistance administrators in the study were mainly colored by the goodness maximization and harm minimization principles. Finally, self-determination and resistance to support were the common thread through all the themes, sometimes making it difficult to delimit the different areas. The work of the social worker involves a holistic approach where one rarely excludes the other, which is reflected in the study's results and analysis.
Keywords: dementia; social work; elderly care; self-determination